Multiomics analysis elucidated molecular mechanism of aromatic amino acid biosynthesis in Akebia trifoliata fruit - Shengfu Zhong; Ju Guan; Chen Chen; Feiquan Tan; Peigao Luo (Frontiers in Plant Science, 2022)
Akebia trifoliata is a novel edible and healthy fruit. Here, we found that this fruit had the highest content of total free amino acids and three aromatic amino acids (AAAs) compared with the other popular fruits, and there was an obvious inverse relationship between AAA and flavonoid levels in various fruit tissues. Multiomics analysis revealed that the evolutionarily strengthened synthetic pathway of all three AAAs, the largely regulating ability conferred by ASP5 in the arogenate pathway and the complementary phenylpyruvate pathway endorsed by ADT of both Phe and Tyr biosynthesis provided reasonable explanations for the high AAA content in the flesh of A. trifoliata fruit. Gene-specific expression could be the main reason for the inverse relationship between AAAs and flavonoids. This study will help us understand the metabolic mechanism of AAAs and to develop A. trifoliata as a fresh fruit crop and medicinal plant by molecular breeding strategies.